Baseline Xpert MTB/RIF ct values predict sputum conversion during the intensive phase of anti-TB treatment in HIV infected patients in Kampala, Uganda: a retrospective study - Namugenyi, Juliet; Musaazi, Joseph; Katamba, Achilles; Kalyango, Joan; Sendaula, Emmanuel; Kambugu, Andrew; Fehr, Jan; Castelnouvo, Barbara; Manabe, Yukari C.; Ssengooba, Willy; Sekaggya-Wiltshire, Christine (BMC Infectious Diseases, 2021)
In resource-limited settings, sputum smear conversion is used to document treatment response. Many People living with HIV (PLHIV) are smear-negative at baseline. The Xpert MTB/RIF test can indirectly measure bacterial load through cycle threshold (ct) values. This study aimed to determine if baseline Xpert MTB/RIF could predict time to culture negativity in PLHIV with newly diagnosed TB. Methods: A subset of 138 PLHIV from the ‘SOUTH’ study on outcomes related to TB and antiretroviral drug concentrations were included. Bacterial load was estimated by Mycobacterium Growth Indicator Tubes (MGIT) culture time-to-positivity (TTP) and Lowenstein Jensen (LJ) colony counts. Changes in TTP and colony counts were analyzed with Poisson Generalised Estimating Equations (GEE) and multilevel ordered logistic regression models, respectively, while time to culture negativity analysed with Cox proportional hazard models. ROC curves were used to explore the accuracy of the ct value in predicting culture negativity. Results: A total of 81 patients (58.7%) were males, median age 34 (IQR 29 ̶ 40) years, median CD4 cell count of 180 (IQR 68 ̶345) cells/μL and 77.5% were ART naive. The median baseline ct value was 25.1 (IQR 21.0 ̶ 30.1). A unit Increase in the ct value was associated with a 5% (IRR = 1.05 95% CI 1.04 ̶ 1.06) and 3% (IRR = 1.03 95% CI 1.03 ̶ 1.04) increase in TTP at week 2 and 4 respectively. With LJ culture, a patient’s colony grade was reduced by 0.86 times (0R = 0.86 95% CI 0.74 ̶ 0.97) at week 2 and 0.84 times (OR = 0.84 95% CI 0.79 ̶ 0.95 P = 0.002) at week 4 for every unit increase in the baseline ct value. There was a 3% higher likelihood of earlier conversion to negativity for every unit increase in the ct value. A ct cut point ≥28 best predicted culture negativity at week 4 with a sensitivity of 91. 7% & specificity 53.7% while a cut point ≥23 best predicted culture negativity at week 8. Conclusion: Baseline Xpert MTB/RIF ct values predict sputum conversion in PLHIV on anti-TB treatment. Surrogate biomarkers for sputum conversion in PLHIV are still a research priority.
Keywords: Mycobacterium tuberculosis; HIV; Xpert MTB/RIF; Baseline ct values; Time to positivity; Colony count